Neurotoxicity and inflammation induced by individual and combined exposure to iron oxide nanoparticles and silver nanoparticles. Issue 1 (11th December 2019) - Yousef, Mokhtar Ibrahim; Abuzreda, Abdelsalam Abdalla; Kamel, Maher Abd EL-Nabi
Abstract : The present study aimed to investigate the neurotoxicity of iron oxide and silver NPs solely or combined. At the molecular level, the exposure to both NPs induced marked DNA fragmentation, downregulation of mtTFA, and upregulation of PGC-1 α expression. Both NPs caused decline in acetylcholine esterase, norepinephrine, serotonin, dopamine, and antioxidants enzymes, while causing an increase in lipid peroxidation, nitric oxide, tumour suppressor gene p53, tumour necrosis factor- α, interleukin-6, acetylcholine, and norepinephrine. NPs exposure was  associated with severe histologic changes in brain architecture. The effect of the combined exposure to both  NPs was more pronounced than each one alone. This study showed that the mechanism of neurotoxicity may involve different pathways including changes in gene expression of mTFA and PGC-1 α, induced DNA fragmentation, deregulated neurotransmitters, oxidative stress and disturbed cytokine production and tumour suppressor protein p53.